STUDY ON MILKABILITY TRAITS OF KANKREJ COWS - Anand, D; Trivedi, M M; Dhami , A J; Divekar , `B S; Patel , À M (Indian Journal of Veterinary Sciences and Biotechnology, 2010)
The study was undertaken on 12 suckled Kankrej cows to investigate the effects of shift of milking, season and milker on milkability traits, viz. let down time, total milking time, milk yield/milking and milk flow rate. The overall mean let down time, total milking time, milk yield/milking and milk flow rate were 67.99 seconds, 262.67 seconds, 3.32 kg and 0.77 kg/minute, respectively. The differences between morning and evening milking were non-significant for let down time, total milking time and milk yield. However, milk flow rate showed significant (P<0.05) variation between morning and evening milkings. Significantly (P<0.01) higher let down time (76.66 seconds) and total milking time (317.61 seconds) were recorded in hot humid season as compared to cold dry season (63.36 and 234.90 seconds). However, average milk yield/milking showed reverse trend, wherein significantly higher (P<0.01) milk yield was recorded in hot humid season (4.02 kg vs 2.97 kg). Milk flow rate was almost similar in both hot humid and cold dry seasons. Differences in let down time, total milking time and milk flow rate in cows milked by different milkers were non-significant. Milk let down time was significantly and positively correlated with total milking time (r - 0.758). Milk yield had highly significant and positive (P<0.01) correlations with both let down time (r = 0.844) and total milking time (r = 0.963). However, milk flow rate was negatively correlated with milking time (r - -0.570).